CFD simulation of the structured packings: A review. Issue 15 (13th October 2019) - Amini, Younes; Nasr Esfahany, Mohsen
ABSTRACT: Extensive usage of the structured packings in various industrial applications has led to comprehensive investigations of their properties and performance. Among various methods of modeling, computational fluid dynamics (CFD) is an efficient approach to present full details of fluid behavior inside structured packings. This review focuses on the application of CFD for investigation and development of the structured packings. Applications of the CFD for the simulation of gas–liquid flow behavior, flow distribution, liquid hold-up, and mass transfer are extensively reviewed. Literature survey of the available CFD studies can provide a comprehensive and descriptive insight about governing mechanisms of fluid flow inside packings and reveals qualitative/quantitative effects of the process variables on the packed system.